A novel turbidimetric immunoassay for fecal calprotectin optimized for routine chemistry analyzers. Issue 4 (15th September 2016) - Nilsen, Tom; Sunde, Kathrin; Hansson, Lars‐Olof; Havelka, Aleksandra Mandic; Larsson, Anders
Abstract : Background: Fecal calprotectin assays are widely used to exclude inflammatory bowel disease (IBD) in patients with suspected IBD. A problem with the fecal calprotectin assays is the rather long test‐turnaround times. A particle enhanced turbidimetric immunoassays (PETIA) for fecal calprotectin would reduce test‐turnaround times and would permit more laboratories to perform the measurements. The aim of this study was to evaluate a new feces calprotectin PETIA. Method: Using routine fecal samples the feces calprotectin PETIA was validated on two chemistry analyzers, Mindray BS‐380 and Cobas 501. Results: The assay is linear in the range 11–2000 μg/g, with a limit of quantitation of approximately 10 μg/g. No antigen excess hook effect was observed up to 10 000–15 000 μg/g depending on the instrument used. The turbidimetric method showed a good agreement with the Bühlmann ELISA. The total coefficient of variation was 3%–8% in the 50–100 μg/g range. Conclusion: The fecal calprotectin PETIA, fCal Turbo, is well suited for rapid analysis of fecal calprotectin on Mindray BS‐380 or Cobas 501 clinical chemistry analyzers. The test results are commutable with Bühlmann fecal MRP8/14 ELISA.